2021
DOI: 10.3389/fped.2021.661025
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Radical “En-Bloc” Resection of Ewing Sarcoma of the Chest Wall and Simultaneous Chest Wall Repair Achieves Excellent Long-Term Survival in Children and Adolescents

Abstract: Introduction: Ewing sarcomas of the chest wall, historically known as “Askin tumors” represent highly aggressive pediatric malignancies with a reported 5-year survival ranging only between 40 and 60% in most studies. Multimodal oncological treatment according to specific Ewing sarcoma protocols and radical “en-bloc” resection with simultaneous chest wall repair are key factors for long-term survival. However, the surgical complexity depends on tumor location and volume and potential infiltrations into lung, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
0
6
0
8
Order By: Relevance
“…Recently some authors reported their experience with bioresorbable plate, which could be a good addition to other available methods to reconstruct the chest wall in children, even if further studies are needed (5,10,11). Relevant papers have been summarized in Table 2 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Recently some authors reported their experience with bioresorbable plate, which could be a good addition to other available methods to reconstruct the chest wall in children, even if further studies are needed (5,10,11). Relevant papers have been summarized in Table 2 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Thoraxwandresektionen mit Rekonstruktion können in Abhängigkeit des Resektionsausmaßes bei Kindern langfristig zu Skoliosen, aber auch zu kosmetischer Entstellung mit psychischen Folgen, chronischen Schmerzen und Aktivitätseinschränkungen führen [6,7,8].…”
Section: Maligne Brustwandtumoren Bei Kindernunclassified
“…advise that resection of the involved rib plus one adjacent rib on either side is necessary for margin control 1 . This has been shown to achieve excellent long‐term survival in children and adolescents, 2 but presents reconstructive challenges. The goals of chest wall reconstruction are protection of the intrathoracic contents, optimization of respiratory mechanics, support for the shoulder and upper extremity and restoration of trunk contour 3 .…”
Section: Figmentioning
confidence: 99%
“…The goals of chest wall reconstruction are protection of the intrathoracic contents, optimization of respiratory mechanics, support for the shoulder and upper extremity and restoration of trunk contour 3 . Typically, a polypropylene mesh and methyl methacrylate (MMA) ‘sandwich’ is used for reconstruction 1–3 . Reliance of surgeon's ‘eye’ and experience can mean that considerable intraoperative adjustments and revisions are required to achieve an optimal functional and cosmetic result.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation